Seroprevalence and Risk Factors of Bovine Viral Diarrhea in Improved Cattle of Chitwan, Nawalpur and Rupandehi Districts of Nepal - Thapa, A.; Acharya, M. P.; Raut, R.; Rimal, S. (Nepalese Veterinary Journal, 2019)
This study was aimed at assessing the prevalence of bovine viral diarrhea (BVD) in improved dairy cattle of Chitwan, Nawalpur and Rupandehi Districts of Nepal. Altogether 92 blood samples were aseptically collected from jugular vein of cattle and transferred to clot activator tube and transported to National Cattle Research Program, Rampur, Chitwan. This cross sectional study was carried out from Mangsir to Magh of 2075 B.S using purposive sampling Serum separation was done by centrifugation @3500 for 5 minutes. The serum was stored at -20°C till ELISA test was done. Serological analysis was done according to the protocol of ID.vet BVD Ab ELISA kit. Data were analyzed using Ms excel and SPSS version 20.0.The seroprevalence of BVD Virus was found to be 7.76%. Provided that no history of vaccination against BVD in cattle was done in the study area, seropositive was due to natural infection. Geographic location as well as sampling method might have contributed to this result. The result indicated lower prevalence along with no statistical significance to breed and age risk factors undertaken during the research. However significant association was observed between abortion history and seropositivity. Hence, there is a need of further research to identify the disease burden and its impact in the agricultural gross domestic products (AGDP).